Tissue Engineering: Biomimetic Concealing of PLGA Microspheres in a 3D Scaffold to Prevent Macrophage Uptake (Small 11/2016). Issue 11 (March 2016) - Minardi, Silvia; Corradetti, Bruna; Taraballi, Francesca; Sandri, Monica; Martinez, Jonathan O.; Powell, Sebastian T.; Tampieri, Anna; Weiner, Bradley K.; Tasciotti, Ennio
Abstract : Avoiding the clearance of drug delivery systems from 3D scaffolds is crucial to preserve the bioactivity of their therapeutic payload. This is accomplished on page 1479, by E. Tasciotti and co‐workers, through a "concealing" strategy: cloaking PLGA microspheres with the type I collagen matrix of a biomimetic scaffold, which enables the control of the production of inflammatory mediators.